Európaizáció a közigazgatási eljárásjogban (Europeanization in the Administrative Procedural Law) - Adrián Fábián; Eszter Fábián (KözigazgatásTudomány, 2024)
The development and changes of national administrative law and national administrative procedural law are not isolated from the development and changes of EU law. Interpreting these changes as a process and tendency allows us to divide the legal development into stages and draw conclusions. Today, it can be said that the harmonization of national administrative procedural rules can be summarized with the concept of Europeanization. Europeanization is thus the result so far of the common development of the administrative procedural rules of the member states, but at the same time, it is – certainly – the current stage of this trend, but not the final stage. Our study deals with this phenomenon's causes, characteristics and expected effects.